Antioxidants in Foods and Its Applications 2018
DOI: 10.5772/intechopen.75069
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Iodine, Selenium, and Silicon in Plant Nutrition for the Increase of Antioxidants in Fruits and Vegetables

Abstract: Iodine, silicon, and selenium are considered elements not essential for the metabolism of plants. However, these elements are vital for humans, and their presence as traces in food is beneficial. The use of I, Si, and Se in the fertilization programs of the plants allows, on the one hand, the mineral biofortification of the crops and, on the other hand, through mechanisms not yet fully understood, the production and accumulation of more antioxidants in the edible organs. This chapter provides an overview about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Antioxidants play protective roles against oxidative stress in plants, with free – OH groups attached to the aromatic ring reducing oxidative damage by scavenging ROS and chelating metals. Generally, increases of secondary metabolites contributed to the improvement of cell responses to oxidative stress in addition to antioxidant activity of fruits which improved their quality 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants play protective roles against oxidative stress in plants, with free – OH groups attached to the aromatic ring reducing oxidative damage by scavenging ROS and chelating metals. Generally, increases of secondary metabolites contributed to the improvement of cell responses to oxidative stress in addition to antioxidant activity of fruits which improved their quality 74 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the combined application of I and Se in low doses can influence the plant positively. This effect can be observed in the crop yields and/or in the concentrations of nutrients, bioactive compounds, and nutraceuticals (Germ et al, 2015;Medrano-Macías et al, 2018). Mao et al (2014) conducted research with soil fertilization, using I and Se.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the antibacterial properties of Se [15][16][17] and iodine [18] have been established. It should also be noted that the concentration of iodine and selenium in the soil is very low (<0.1 to 150 mg kg −1 and 0.05 to 1.5 mg kg −1 , respectively) [13]. In previous studies, it has been found that pre-treatment with a 1% I-Se solution signifi cantly damages P. syringae pv.…”
mentioning
confidence: 92%
“…At the same time, the search for and research of elements and compounds with antimicrobial activity in plants are going on. In this sense, the study of the antimicrobial and physiological eff ects of both individual elements and compounds that are necessary for humans is of interest [12], in particular I and Se [13]. Th ese elements are often used in biofortifi cation programs in order to enrich plant raw materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation